Ultrastructural study of the ovary of the sugarcane spittlebug Mahanarva fimbriolata (Hemiptera) - Caperucci, Debora; Camargo-Mathias, Maria Izabel (Elsevier B.V., 2006)
The present study describes the ultrastructure of meroistic telotrophic ovaries of the sugarcane spittlebug Mahanarva fimbriolata. In this type of ovary, nurse cells, oogonia, and prefollicular tissue are located at the terminal (distal) regions or tropharium of ovarioles. Oocytes in different developmental stages, classified from I to V, are observed in the vitellarium. Stage I oocytes do not exhibit intercellular spaces in the follicular epithelium, suggesting that synthesis and production of yolk during this stage occurs only through endogenous processes. Small yolk granules of different electron densities are present in the cytoplasm. Few lipid droplets are observed. Stage 11 oocytes exhibit small intercellular spaces in the follicular epithelium. More protein as well as lipid yolk granules are observed in the cytoplasm. In stage III oocytes, intercellular spaces in the follicular epithelium are larger than those observed in the previous stage. Electrondense protein granules of various sizes, larger than those observed in stage 11 oocytes predominate in the cytoplasm. Smaller lipid droplets are also present. In stage IV oocytes, the follicular epithelium exhibits large intercellular spaces. Our data clearly indicate that the opening of these spaces in the follicular epithelium of M. fimbriolata oocytes increases as the intake of exogenous proteins intensifies, that is, in stages IV and Voocytes. During these stages, granular yolk becomes viscous due to the lysis of granules. In stage Voocytes, viscous yolk predominates in the cytoplasm. This type of yolk, however, has not been described for other orders of insects. The chorion of M. fimbriolata oocytes consists of an external layer (exochorion) and an internal one (endochorion), which is in direct contact with the oocyte. Numerous small pores that probably facilitate oxygenation of the internal structures inside the eggs are observed in the exochorion. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mahanarva fimbriolata; ovary; ultrastructure; vitellogenesis